2022
DOI: 10.1002/anie.202204736
|View full text |Cite
|
Sign up to set email alerts
|

On‐Surface Synthesis of a Nitrogen‐Doped Graphene Nanoribbon with Multiple Substitutional Sites

Abstract: Doped graphene nanoribbons (GNRs) with heteroatoms are a principal strategy to fine-tune the electronic structures of GNRs for future device applications. Here, we successfully synthesized the N = 9 nitrogen-doped armchair GNR on the Au(111) surface. Due to the flexibility of precursor molecules, three different covalent bonds (CÀ C, CÀ N, NÀ N) are formed in the GNR backbone. Scanning tunneling spectroscopy analysis together with band structure calculations reveals that the band gap of the N-9-AGNRs (CÀ C) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…The shift could be attributed to the rotation of the single bond between two benzene rings of BPN leading to planarity and conjugation decrease . TP-BPyN COF and TP-BPyN PCOF both present a further tiny blue shift than that of TP-BPN COF, which could be related to the influence of the pyridine N atoms extending the bandgap of the COFs . Based on UV–vis DRS, the band gaps were calculated from the Kubelka–Munk function .…”
Section: Resultsmentioning
confidence: 99%
“…The shift could be attributed to the rotation of the single bond between two benzene rings of BPN leading to planarity and conjugation decrease . TP-BPyN COF and TP-BPyN PCOF both present a further tiny blue shift than that of TP-BPN COF, which could be related to the influence of the pyridine N atoms extending the bandgap of the COFs . Based on UV–vis DRS, the band gaps were calculated from the Kubelka–Munk function .…”
Section: Resultsmentioning
confidence: 99%
“…After the development of on-surface synthesis of GNRs, Cai et al had introduced N dopants at edges of the chevron-type GNRs, which formed the p–N-GNR heterostructures between the pristine segments and the N-doped segments by codepositing the pristine and N-doped molecule precursors . A recent experiment suggested that N dopants formed the pyridinic configuration but not the graphitic along the armchair edges (Figure a), where the edge dopants could only shift the Fermi level without significantly changing the band gap size, consistent with previous theoretical results . Introducing a superlattice of isoelectronic dopants along the zigzag edges had been confirmed as an effective way to stabilize and decouple the highly reactive spin-polarized edge states from the substrate (Figure b), where the ferromagnetically ordered edge states induced a giant spin splitting of low-lying nitrogen lone-pair flat bands by an exchange field (∼850 T).…”
Section: Peroiodic Heteroatom Substitutionmentioning
confidence: 99%
“…Since the pioneering bottom-up fabrication of armchair GNR (7-AGNR) reported by Cai et al in 2010 [124], on-surface synthesis strategy has displayed its capability in the subtle regulation of the topologies and consequently precise steering of the electronic properties. So far, GNRs with AGNRs and zigzag edges [124][125][126], chiral GNRs [121,127,128], heteroatom-doped GNRs [120,[129][130][131], and extended nanoporous graphenes [132,133] have been precisely synthesized on surfaces and extensively investigated by virtue of SPM techniques. Several strategies turn out to be effective in tuning the band gaps.…”
Section: Gnrs and Other π-Conjugated Polymer Chainsmentioning
confidence: 99%